2020
DOI: 10.1038/s41389-020-00258-y
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-CpG-binding protein 2 drives the Furin/TGF-β1/Smad axis to promote epithelial–mesenchymal transition in pancreatic cancer cells

Abstract: Methyl-CpG-binding protein 2 (MeCP2) has been characterized as an oncogene in several types of cancer. However, its precise role in pancreatic ductal adenocarcinoma (PDAC) remains unclear. Hence, this study aimed to evaluate the potential role of MeCP2 in pancreatic cancer progression. We found that MeCP2 was upregulated in pancreatic cancer tissues, enhanced migration, invasion, and proliferation in pancreatic cancer cells, and promoted tumorigenesis. Further evidence revealed that MeCP2 remarkably increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Luo and Ge [ 33 ] showed that MeCP2 promotes colorectal cancer metastasis by modulating ZEB1 transcription. In pancreatic cancer, MeCP2 drove the Furin/TGF‐β1/Smad axis to increase epithelial–mesenchymal transition in pancreatic cancer cells [ 34 ]. In our present study, TCGA and GTEX data revealed that MeCP2 expression was remarkably higher in HCC tissues and was correlated with patients' survival rate; these results were confirmed in our 36 paired HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Luo and Ge [ 33 ] showed that MeCP2 promotes colorectal cancer metastasis by modulating ZEB1 transcription. In pancreatic cancer, MeCP2 drove the Furin/TGF‐β1/Smad axis to increase epithelial–mesenchymal transition in pancreatic cancer cells [ 34 ]. In our present study, TCGA and GTEX data revealed that MeCP2 expression was remarkably higher in HCC tissues and was correlated with patients' survival rate; these results were confirmed in our 36 paired HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent experimental evidence has shown that MeCP2 contributes to cancer proliferation and metastasis, 31,46,47 the biological mechanism of MeCP2 on carcinogenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent experimental evidence has shown that MeCP2 contributes to cancer proliferation and metastasis, 31,46,47 the biological mechanism of MeCP2 on carcinogenesis is still unclear. Here, we found a novel mechanism through indirect influence on m 6 A methylation modification.…”
Section: Discussionmentioning
confidence: 99%
“…But their roles in in PC are not well understood except a few members ( 35 ). MeCP is the first identified MBD domain-containing protein and considered to be an oncogene in PC, promoting EMT in PC cells ( 36 ). However, MBD3 plays a suppressive role in PC.…”
Section: Dna Methylationmentioning
confidence: 99%